Pan-Genome-Based Analysis as a Framework for Demarcating Two Closely Related Methanotroph Genera Methylocystis and Methylosinus - Igor Y. Oshkin; Kirill K. Miroshnikov; Denis S. Grouzdev; Svetlana N. Dedysh (Microorganisms, 2020)
The Methylocystis and Methylosinus are two of the five genera that were included in the first taxonomic framework of methanotrophic bacteria created half a century ago. Members of both genera are widely distributed in various environments and play a key role in reducing methane fluxes from soils and wetlands. The original separation of these methanotrophs in two distinct genera was based mainly on their differences in cell morphology. Further comparative studies that explored various single-gene-based phylogenies suggested the monophyletic nature of each of these genera. Current availability of genome sequences from members of the Methylocystis/Methylosinus clade opens the possibility for in-depth comparison of the genomic potentials of these methanotrophs. Here, we report the finished genome sequence of Methylocystis heyeri H2T and compare it to 23 currently available genomes of Methylocystis and Methylosinus species. The phylogenomic analysis confirmed that members of these genera form two separate clades. The Methylocystis/Methylosinus pan-genome core comprised 1173 genes, with the accessory genome containing 4941 and 11,192 genes in the shell and the cloud, respectively. Major differences between the genome-encoded environmental traits of these methanotrophs include a variety of enzymes for methane oxidation and dinitrogen fixation as well as genomic determinants for cell motility and photosynthesis.